Long-term evolution of N-terminal pro-brain natriuretic peptide levels and exercise capacity in 132 left ventricular assist device recipients. (10th February 2022) - Van Edom, Charlotte; Jacobs, Steven; Fresiello, Libera; Vandersmissen, Katrien; Vandenbriele, Christophe; Droogné, Walter; Meyns, Bart
Abstract: OBJECTIVES: N-terminal pro-brain natriuretic peptide (NT-proBNP) is a widely used biomarker in clinical practice in the context of heart failure. Little is known about the long-term evolution of NT-proBNP levels in left ventricular assist device (LVAD) recipients. Besides this, the potential correlation of NT-proBNP with exercise capacity on the long term after LVAD implantation has not been previously studied. METHODS: We retrospectively analysed 132 single-centre LVAD recipient records (HeartMate II/III; HeartWare; between March 2007 and January 2018; mean follow-up 559 days). Blood samples, 6-min walking test (6MWT) and maximal cardiopulmonary exercise test were performed in a standardized way. RESULTS: Pre-LVAD NT-proBNP levels were increased (9736 ± 1072 ng/l) and dropped significantly after implantation [14 days: 4360 ± 545 ng/l ( P < 0.0001), 6 months: 1485 ± 139 ng/l ( P < 0.0001)]. Afterwards a steady state was reached during follow-up (after 1 year: 1592 ± 214 ng/l, after 5 years: 1679 ± 311 ng/l). Submaximal exercise capacity significantly improved postoperatively [percentage of the predicted distance walked during the 6MWT 50 ± 2% (0–3 months); 61 ± 2% (3–6 months, P < 0.001)], with a steady state afterwards [66 ± 2% (6–12 months, P = 0.08); 64 ± 3%, P = 0.70 later on]. We found a gradual increment of percentage of the expected peak oxygen consumption postoperatively [44 ± 2% (0–3 months); 49 ± 2% (3–6 months); 52 ± 2% (6–12 months); 53 ± 1% (after 12 months)] with a significant improvement between 0 and 3 months versus after the first year on LVAD. Furthermore, we showed a significant moderate correlation between NT-proBNP levels and results at both the 6MWT (correlation coefficient: −0.31, P < 0.0001) and cardiopulmonary exercise testing (correlation coefficient: −0.28, P < 0.0001). CONCLUSIONS: NT-proBNP decreased on LVAD support. We showed that submaximal (6MWT) and maximal exercise capacity (cardiopulmonary exercise testing) improve after LVAD implantation and demonstrated an inverse correlation of both tests with NT-proBNP levels. Abstract : Heart failure with reduced ejection fraction (HFrEF) remains a complex syndrome involving a multitude of interacting pathophysiologic mechanisms.